2017
DOI: 10.1364/oe.25.010743
|View full text |Cite
|
Sign up to set email alerts
|

Optimization in nanocoated D-shaped optical fiber sensors

Abstract: Nanocoated D-shaped optical fibers have been proven as effective sensors. Here, we show that the full width at half minimum (FWHM) of lossy mode resonance can be reduced by optimizing the nanocoating width, thickness and refractive index. As a counterpart, several resonances are observed in the optical spectrum for specific conditions. These resonances are caused by multiple modes guided in the nanocoating. By optimizing the width of the coating and the imaginary part of its refractive index, it is possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…There, it is interesting to observe that, for the SnO 2 coating, the first TE LMR is present at about 570 nm as a side lobe and the TM LMR is visible at a shorter wavelength (450 nm), as observed in other works [28] (the presence of both TE and TM LMRs is explained by the fact that in the sputtering machine the polarizer was not used due to the difficulty of protecting it during deposition). With respect to the CuO spectrum, the resonance is wider.…”
Section: Resultssupporting
confidence: 64%
“…There, it is interesting to observe that, for the SnO 2 coating, the first TE LMR is present at about 570 nm as a side lobe and the TM LMR is visible at a shorter wavelength (450 nm), as observed in other works [28] (the presence of both TE and TM LMRs is explained by the fact that in the sputtering machine the polarizer was not used due to the difficulty of protecting it during deposition). With respect to the CuO spectrum, the resonance is wider.…”
Section: Resultssupporting
confidence: 64%
“…ITO has been used on multimode fibers of different diameters [7,19,20], as well as D-shaped fibers [16,21] or glass slide in Kretschmann configuration [22]. Most authors have studied ITO as a coating material by fabricating a thin film by means of sputtering [16,23,24] or thermal evaporation technique [7], however other techniques such as dip coating have also been used [19]. While most studies have been focused on homogeneous ITO thin films, some works have been reported using nanoparticle-based ITO coatings [7].…”
Section: Indium Tin Oxide (Ito)mentioning
confidence: 99%
“…coating material by fabricating a thin film by means of sputtering [16,23,24] or thermal evaporation technique [7], however other techniques such as dip coating have also been used [19]. While most studies have been focused on homogeneous ITO thin films, some works have been reported using nanoparticle-based ITO coatings [7].…”
Section: Indium Tin Oxide (Ito)mentioning
confidence: 99%
“…The metallic wires support multiple modes, which are responsible for the increased number of resonant peaks that result in the sensor with different values of refractive index detection range and operating wavelengths [62]. Nanocoated D-shaped optical fibers were constructed for sensing applications with a sensitivity of 1566 nm/RIU [63]. A single mode D-shaped fiber is used for sensing the RI monitoring of liquid with linearity up to 0.984 [64].…”
Section: Conventional Optical Fiber Sensorsmentioning
confidence: 99%